A 40 ka record of temperature and permafrost conditions in northwestern Europe from noble gases in the Ledo-Paniselian Aquifer (Belgium) - Blaser, Petra Corinne; Kipfer, Rolf; Loosli, Heinz Hugo; Walraevens, Kristine; Camp, Marc van; Aeschbach-Hertig, Werner (Journal of Quaternary Science, 2010)
ISSN:0267-8179 ISSN:1099-1417